N – Topological Space and Its Applications in Artificial Neural Networks - Tawfiq, L.N.M.; Majeed, R.N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
In this paper we give definitions, properties and examples of the notion of type Ntopological space. Throughout this paper N is a finite positive number, N 2. The task of this paper is to study and investigate some properties of such spaces with the existence of a relation between this space and artificial Neural Networks (ïNN’S), that is we applied the definition of this space in computer field and specially in parallel processing